Domestic Manufacturing Trends within Developing Nations Following WTO Accession - Tanoos, James J. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
The shift in the new members of the World Trade Organization from developed countries to underdeveloped countries has resulted in vastly increased access to new export markets for these underdeveloped countries. As such, the process of accession into the WTO has been increasingly coveted by underdeveloped countries, and numerous studies highlighted increased trade in the years after WTO accession for a new member. Underdeveloped WTO member countries, in particular China, have received a unprecedented scrutiny in international trade, as their overall economies have greatly benefited, prompting anti-dumping grievances from developed countries due to their massive success in the export of manufactured goods. This has changed the purview of the WTO from trade dispute resolution to trade protection. Nevertheless, the economic success accruing in China after WTO membership in 2001 has been so substantial that other countries are devoting vast resources to seeking and navigating through the accession process, provoking coinciding outcries from developed countries for a more stringent WTO accession process because of protectionist concerns about the dumping of products from underdeveloped countries into their domestic markets. This study will assess manufacturing-related GDP in developing countries after WTO accession in order to determine the validity of these recent complaints directed at the WTO.